Toward Understanding the Molecular Role of SNX27/Retromer in Human Health and Disease - Chandra, Mintu; Kendall, Amy K.; Jackson, Lauren P. (Frontiers in Cell and Developmental Biology, 2021)
Aberrations in membrane trafficking pathways have profound effects in cellular dynamics of cellular sorting processes and can drive severe physiological outcomes. SNX27 is a metazoan-specific Sorting Nexin protein from the PX-FERM domain family and is required for endosomal recycling of many important transmembrane receptors. Multiple studies have shown SNX27-mediated recycling requires association with retromer, one of the best-known regulators of endosomal trafficking. SNX27/retromer downregulation is strongly linked to Down’s Syndrome (DS) via glutamate receptor dysfunction and to Alzheimer’s Disease (AD) through increased intracellular production of amyloid peptides from amyloid precursor protein (APP) breakdown. SNX27 is further linked to addiction via its role in potassium channel trafficking, and its over-expression is linked to tumorigenesis, cancer progression, and metastasis. Thus, the correct sorting of multiple receptors by SNX27/retromer is vital for normal cellular function to prevent human diseases. The role of SNX27 in regulating cargo recycling from endosomes to the cell surface is firmly established, but how SNX27 assembles with retromer to generate tubulovesicular carriers remains elusive. Whether SNX27/retromer may be a putative therapeutic target to prevent neurodegenerative disease is now an emerging area of study. This review will provide an update on our molecular understanding of endosomal trafficking events mediated by the SNX27/retromer complex on endosomes.